The feminist standpoint theory reader: Intellectual and political controversies - Harding, Sandra G. (Routledge, 2004)
Leading feminist scholar and one of the founders of Standpoint Theory, Sandra Harding brings together the biggest names in the field–Dorothy Smith, Donna Haraway, Patricia Hill Collins, Nancy Hartsock and Hilary Rose–to not only showcase the most influential essays on the topic but to also highlight subsequent interrogations and developments of these approaches from a wide variety of disciplines and intellectual and political positions.
https://books.google.ca/books?id=qmSySHvIy5IC&printsec=frontcover&hl=fr&source=gbs_ViewAPI&redir_esc=y#v=onepage&q&f=false
Keywords: approches et analyses; cours; discipline; fem1000; har4600; incontournable; interdisciplinarité; point de vue situé; pol4212; premier cycle; privilèges; ressource en ligne; sciences humaines; systèmes d'oppressions; épistémologie

Standpoint theory, situated knowledge and the situated imagination - Stoetzler, Marcel; Yuval-Davis, Nira (Feminist Theory, 2002)
The aim of the article is to further assess and develop feminist standpoint theory by introducing the notion of the ‘situated imagination’ as constituting an important part of this theory as well as that of ‘situated knowledge’. The article argues that the faculty of the imagination constructs as well as transforms, challenges and supersedes both existing knowledge and social reality. However, like knowledge, it is crucial to theorize the imagination as situated, that is, as shaped and conditioned (although not determined) by social positioning.
Number: 3 https://journals-sagepub-com.proxy.bibliotheques.uqam.ca/doi/pdf/10.1177/146470002762492024
Keywords: approches et analyses; cours; discipline; fem1000; justice sociale; militance; mouvements sociaux; point de vue situé; premier cycle; ressource en ligne; sciences humaines; thématiques; théories féministes; épistémologie

Provoking feminisms - Allen, Carolyn; Howard, Judith A. (The University of Chicago Press, 2000)
Un livre stimulant et incisif, Provoking Feminisms est une collection d'essais, de commentaires et de réponses sur certaines des questions les plus controversées de la théorie féministe d'aujourd'hui. Des conversations spécifiques sont centrées sur des sujets de débat tels que la théorie du point de vue féministe ; le genre comme catégorie analytique ; problèmes de "différence" sexuelle ; et la vie privée et les représentations du personnel. Chaque échange parle puissamment des enjeux actuels au cœur de l'érudition féministe et comprend des discussions à partir d'un échantillon de disciplines : théorie politique/sociale, philosophie, sociologie, études culturelles et théorie critique. Intense et rigoureux, Provoking Feminisms est un ouvrage crucial pour quiconque s'intéresse à l'état de l'érudition féministe contemporaine.
Keywords: anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; point de vue situé; sciences humaines; thématiques; épistémologie

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (L'Harmattan, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie